Spectrophotometric Estimation of Ritodrine Hydrochloride in Pharmaceutical Formulations - Bhanu Prasad, A.; Rami Reddy, N.; Chakravarthy, I.E. (Asian Journal of Chemistry, 2016)
A simple, accurate and economical procedure for estimation of ritodrine hydrochloride (RTH) in pharmaceutical formulations has been developed. In this method, the ritodrine hydrochloride was brominated with bromate-bromide mixture under strong acidic condition. After bromination, the excess brominating mixture (bromate-bromide) was reacted with potassium iodide to produce stable yellow colour of KI3 complex. The absorbance of the yellow colour was measured at 350 nm against distilled water as blank. There is no interference from any common pharmaceutical additives. The proposed method is simple, sensitive and economical for the estimation of ritodrine hydrochloride in bulk drug and pharmaceutical formulations.